2017
DOI: 10.3390/s17071627
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyography and Torque during FES-Evoked Muscle Contractions to Fatigue in Individuals with Spinal Cord Injury

Abstract: A mechanomyography muscle contraction (MC) sensor, affixed to the skin surface, was used to quantify muscle tension during repetitive functional electrical stimulation (FES)-evoked isometric rectus femoris contractions to fatigue in individuals with spinal cord injury (SCI). Nine persons with motor complete SCI were seated on a commercial muscle dynamometer that quantified peak torque and average torque outputs, while measurements from the MC sensor were simultaneously recorded. MC-sensor-predicted measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In the field of rehabilitation, EMS has been utilized to treat impaired muscle contraction caused by neuromuscular injuries. Various force response models [ 27 , 28 , 29 , 30 ] with sensors to measure level of muscle contraction, such as electromyography (EMG) [ 31 , 32 ], mechanomyography (MMG) [ 33 , 34 ], and piezoresistive sensors [ 35 , 36 , 37 , 38 , 39 ], have been proposed to precisely control the contraction of impaired muscles in EMS-based rehabilitation. Although these models can represent the nonlinear features of the force response with respect to the various parameters of an electrical stimulation, it remains difficult to apply these models to haptic applications because of the discrepancy of target muscles.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of rehabilitation, EMS has been utilized to treat impaired muscle contraction caused by neuromuscular injuries. Various force response models [ 27 , 28 , 29 , 30 ] with sensors to measure level of muscle contraction, such as electromyography (EMG) [ 31 , 32 ], mechanomyography (MMG) [ 33 , 34 ], and piezoresistive sensors [ 35 , 36 , 37 , 38 , 39 ], have been proposed to precisely control the contraction of impaired muscles in EMS-based rehabilitation. Although these models can represent the nonlinear features of the force response with respect to the various parameters of an electrical stimulation, it remains difficult to apply these models to haptic applications because of the discrepancy of target muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) has been widely used to cause muscle contraction in people with SCI through electrical pulses, which trigger action potentials, applied on the surface of the skin. 10 Recently, hybrid neuroprostheses have utilized the efficiency of NMES to restore the movements of paralyzed limbs in people with SCI. 11,12 Hybrid neuroprostheses work through the combination of muscle activation by NMES with electromechanical actuation of a passive or active orthosis to generate patterns of movements.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) has been widely used to cause muscle contraction in people with SCI through electrical pulses, which trigger action potentials, applied on the surface of the skin . Recently, hybrid neuroprostheses have utilized the efficiency of NMES to restore the movements of paralyzed limbs in people with SCI .…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between MC sensor signal and muscle force as well as a close-to-zero delay between the peak muscle force and MC sensor signal was shown in upper trapezius muscle during a low-severity frontal impact [41]. Mohamad et al [42] evaluated the sensor using functional electrical stimulation. A strong linear correlation between MC sensor measurements and dynamometer isometric knee torque suggested that the MC sensor is able to detect different contraction levels and fatigue of the rectus femoris muscle among individuals with spinal cord injury [42].…”
Section: Introductionmentioning
confidence: 99%
“…Mohamad et al [42] evaluated the sensor using functional electrical stimulation. A strong linear correlation between MC sensor measurements and dynamometer isometric knee torque suggested that the MC sensor is able to detect different contraction levels and fatigue of the rectus femoris muscle among individuals with spinal cord injury [42].…”
Section: Introductionmentioning
confidence: 99%